Construction of Dystopia in Black Mirror: Hated in the Nation - Sheila Adena Putri; Nia Nafisah (Universitas Pendidikan Indonesia (UPI), 2020)
In this early emergence, dystopia is not only built by authoritarian oppression but it can be constructed by every individual in the society. This paper intended to analyze how dystopia is constructed through equal power in James Hawes’s 2016 series entitled Black Mirror, particularly in Hated in the Nation episode. A number of issues in this episode are analyzed by Foucault’s power relation theory. In order to determine whether the power network in the society creates dystopia or not, critical dystopia theory is presented by Booker (1994) and Moylan (2000). Since the main causes of dystopia in this episode are technology and social media, theory about technology progress and human regress is proposed by Jonas in Durdan (2013). The data were collected by sorting out some frames and dialogs throughout the episode. It is found that the vicious cycle of hatred is difficult to break so it creates a deteriorating society. The analysis is expected to contribute other elements in postmodern dystopia narrative.Keywords: Black Mirror, Dystopia, Mass Media, Postmodern Dystopia, Power Relation.